MENTION OF POETS AT "MAJMUAYI SHAYORON" - Tojixon Toshboltayeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the information presented about poets and their creative activities in the Kokand literary environment was researched by the talented poet and tazkiranavis Fazli Namangani on the basis of the "Majmuai shoiron". Fazli’s skill as a was analyzed.